Contribution of Leg Muscle Strength and Hip Flexibility Between the Dominant and Non-Dominant Feet to Longpass Ability in Soccer - Rifqi, Muhammad Alif (Universitas Pendidikan Ganesha, 2023)
The purpose of this study was to determine the contribution of leg muscle strength and hip flexibility between the dominant and non-dominant legs on long pass ability in soccer. This study uses a non-experimental method with a quantitative descriptive approach. The population in this study were 98 students of SSB Bina Pakuan. The sampling technique used purposive sampling technique, the number of samples in this study were 22 students. The instruments in this study were 1) leg muscle strength with Leg Extension, 2) hip flexibility with Goniometer, 3) long pass ability using the long pass barrow test. data analysis technique in this study is to use multiple linear regression analysis. The results of this study are: 1) there is a contribution of dominant leg muscle strength to longpass ability, 2) there is no contribution of non-dominant leg muscle strength to longpass ability, 3) there is no contribution of dominant leg hip flexibility to longpass ability, 4) no there is a contribution of non-dominant leg hip flexibility to longpass ability, 5) there is a joint contribution of leg muscle strength and dominant leg hip flexibility to longpass ability, 6) there is a joint contribution of leg muscle strength and hip flexibility of non-dominant leg on long pass capability. the researcher hopes that future researchers can find ways to develop a player's dominant and non-dominant feet. Also found an aspect that might be able to contribute more in improving the ability of a soccer player, especially in the long pass ability.